2017
DOI: 10.1111/febs.14133
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐30a increases MDSC differentiation and immunosuppressive function by targeting SOCS3 in mice with B‐cell lymphoma

Abstract: Myeloid-derived suppressor cells (MDSCs), including granulocytic (G)-MDSCs and monocytic (M)-MDSCs, play a critical role in tumor-induced T cell tolerance. MDSC immunosuppressive function and differentiation are significantly promoted in patients and B-cell lymphoma model mice. However, the mechanisms regulating these processes remain largely unclear. In the present study, we observed increased microRNA (miR)-30a expression both in G-MDSCs and in M-MDSCs from B cell lymphoma model mice. After transfection with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…5). Consistent with our data, during the preparation of this article, a paper published by Xu and colleagues revealed that miR-30a-5p directly targets the 3= UTR of SOCS3 and manipulates the expression of SOCS3 in mouse B cell lymphoma (55). Importantly, we detected decreased expression of miR-30a-5p and increased expression of SOCS1 and SOCS3 in TGEV-infected ileum.…”
Section: Discussionsupporting
confidence: 91%
“…5). Consistent with our data, during the preparation of this article, a paper published by Xu and colleagues revealed that miR-30a-5p directly targets the 3= UTR of SOCS3 and manipulates the expression of SOCS3 in mouse B cell lymphoma (55). Importantly, we detected decreased expression of miR-30a-5p and increased expression of SOCS1 and SOCS3 in TGEV-infected ileum.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, ADAR1 overexpression significantly reduced IL-6 levels in the spleen, consistent with IL-6 function as the main inflammatory factor, which attenuates the inflammatory response in sepsis that is inhibited by ADAR1. Previous studies have confirmed that SOCS3 is targeted by miR-30a [14,15]. However, the specific mechanism by which ADAR1 reduces IL-6 expression and alleviates sepsis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Suppressor of cytokine signaling 3 (SOCS3) is a feedback inhibitor of the Janus kinase (JAK)/signal sensor and transcriptional activation 3 (STAT3) signaling pathway, which mediates the signal transduction of many cytokines and has been implicated in multiple infectious and inflammatory diseases [12]. Studies have shown that SOCS3 is regulated by miR-30a and miR-30a-5p [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed that miR-30a as a member of the miR-30 family increases the differentiation of MDSCs and their immunosuppressive activity through regulating SOCS3 in B-cell lymphoma model mice. Xu et al ( 82 ) detected augmented expression of miR-30a in PMN-MDSCs and M-MDSCs in mice with B cell lymphoma. MicroRNA-30a targets SOCS3, which is a JAK2/STAT3 pathway regulator.…”
Section: Micro Rnasmentioning
confidence: 99%